Biomedicine and human rights. The Oviedo Convention and its additional protocols - Council of Europe (Strasbourg, 2009)
"The Convention on Human Rights and Biomedicine, also referred to as the "Oviedo Convention", celebrated the 10th anniversary of its entry into force in 2009. This legally binding instrument aims to protect the integrity, dignity and identity of all human beings and guarantees everyone, without discrimination, the respect for their rights and fundamental freedoms with regard to the application of biology and medicine. It shares with the European Convention on Human Rights the same underlying approach and many ethical principles, and provides a general framework for the protection of fundamental rights and freedoms in the field of biomedicine. The Oviedo Convention also addresses new challenges in biomedicine that are brought about by technological and scientific developments, making it a reference text for patient rights at the European level. The principles laid down in the Oviedo Convention were further developed and complemented in additional protocols in specific fields: prohibition of cloning of human beings, transplantation of organs and tissues of human origin, and biomedical research and genetic testing for health purposes. The texts presented in this publication form a unique legally binding set of instruments at the international level."